Interaction of precipitation, recovery and recrystallization in the Mo-Hf-C alloy MHC studied by multipass compression tests. (June 2018) - Siller, M.; Lang, D.; Schatte, J.; Knabl, W.; Clemens, H.; Maier-Kiener, V.
Abstract: The interaction between strain-induced precipitation, recovery and recrystallization governs the properties of the particle strengthened Mo-Hf-C alloy MHC. Complex, multi-staged thermomechanical processes have become the key approach for further improvement of the high temperature properties of MHC products within recent years. An investigation of those processes, including a wide field of parameters, usually turns out to be both difficult and time consuming. With multi-pass compression tests it is possible to analyze complex thermomechanical processes on small scale samples in a straightforward manner. The evaluation of the gathered information is demonstrated and the results are compared to microstructural investigations, conventional mechanical tests as well as relevant literature. Furthermore, the influence of different particle size distributions in MHC is interpreted. Precipitation between individual deformation steps resulted in minor additional hardening of the final material. Intermediate recrystallization during the thermomechanical processing showed high softening and ductilization of the final condition. Graphical abstract: Highlights: Multipass compression tests are used to study the interaction of precipitation, recovery and recrystallization in the Alloy MHC. Microstructural investigations reveal the resulting particle size distributions from different thermomechanical processes. Mechanical tests show the impact of different particle size distributions on the deformation behavior of the material.